Founder representation and effective population size in old versus young breeds—genetic diversity of Finnish and Nordic Spitz. (10th March 2017) - Kumpulainen, M.; Anderson, H.; Svevar, T.; Kangasvuo, I.; Donner, J.; Pohjoismäki, J.
Summary: Finnish Spitz is 130‐year‐old breed and has been highly popular in Finland throughout its history. Nordic Spitz is very similar to Finnish Spitz by origin and use, but is a relatively recent breed with much smaller population size. To see how breed age and breeding history have influenced the current population, we performed comprehensive population genetic analysis using pedigree data of 28, 119 Finnish and 9, 009 Nordic Spitzes combined with genomewide single nucleotide polymorphism (SNP) data from 135 Finnish and 110 Nordic Spitzes. We found that the Finnish Spitz has undergone repeated male bottlenecks resulting in dramatic loss of genetic diversity, reflected by 20 effective founders ( f a ) and mean heterozygosity ( Hz ) of 0.313. The realized effective population size in the breed based on pedigree analysis ( N ¯ e c ) is 168, whereas the genetic effective population size ( N eg ) computed the decay of linkage disequilibrium ( r 2 ) is only 57 individuals. Nordic Spitz, although once been near extinction, has not been exposed to similar repeated bottlenecks than Finnish Spitz and had f a of 27 individuals. However, due to the smaller total population size, the breed has also smaller effective population size than Finnish Spitz ( N ¯ e c = 98 and N eg = 49). Interestingly, the r 2 data show that the effective population size has contracted dramatically since the establishment of the breed, emphasizing the role of breed standards as constrains for the breeding population. Despite the small population size, Nordic Spitz still maintains SNP heterozygosity levels similar to mixed breed dogs (mean Hz = 0.409). Our study demonstrates that although pedigree analyses cannot provide estimates of the present diversity within a breed, the effective population sizes inferred from them correlate with the genotyping results. The genetic relationships of the northern Spitz breeds and the benefits of the open breed registry are discussed.